INVITRO ACTION OF VASOPRESSIN ON WATER-ABSORPTION BY RAT COLON - Vicentinipaulino, MLM (Associação Brasileira de Divulgação Científica (ABRADIC), 1992)
The action of vasopressin on water absorption was studied in vitro in the colon of rats, weighing approximately 250 g. Everted sacs of intestinal segments (ascending and descending colons) prepared with mucosa only were used. Vasopressin (10 mM) significantly stimulated water absorption in both the proximal (4.85 +/- 3.78 vs 1.51 +/- 1.16 ml/mg) and distal (10.39 +/- 3.52 vs 7.22 +/- 3.58 ml/mg) colon, which corresponds to an increase of 220% and 50%,respectively. The results indicate the need for a study of the possible physiological function of vasopressin in enhancing intestinal water absorption, when it is released in response to plasma hyperosmolarity.
Keywords: VASOPRESSIN; WATER ABSORPTION; COLON; RATS